SCHELLING'S ONTOLOGY OF POWERS - Alderwick, Charlotte (New perspectives in ontology., 2021)
Charlotte Alderwick presents Schelling's ontology as fundamentally power-based. She demonstrates that this ontology enables his unique conception of human freedom outlined in the 'Freedom' essay and can usefully problematise and supplement contemporary work on power-based ontologies.